Effectiveness of low-cost reminder package combined with case-based health education to improve hypertensive patients’ medication adherence: a clustered randomized controlled trial - Shen, Y; Wang, T; Gao, M; Zhu, X; Zhang, X; He, C; Li, Y; Sun, X (Dove Medical Press, 2019)
Purpose: Medication adherence (MA) is a key factor for hypertensive patients’ blood pressure control and forgetfulness is one of the main reasons that cause medication non-adherence. If effective, low-cost reminder package (LCRP) has great potentials for large-scale promotion. Therefore, this study aims to evaluate the effectiveness of combining LCRP and health education to improve MA among hypertensive patients. Patients and methods: A clustered randomized controlled trial was performed in Beijing. A total of 518 hypertensive patients recruited from 8 community health care centers were randomized to receive LCRP combined with case-based health education or usual care. Randomization was performed at community level. Multilevel modeling was used to evaluate the study effect. Results: MA scores did not differ significantly at baseline between the intervention group and the control group. The results of multilevel modeling indicated that MA scores increased more in the intervention group, and the intervention effect on MA was 0.287 (95% CI: [0.103, 0.471], P=0.002). Patients’ systolic blood pressure (SBP) and diastolic blood pressure (DBP) were not improved (SBP: difference=0.536, 95% CI [−3.207, 4.278]; DBP: difference=−0.927, 95% CI [−3.283, 1.428]). Conclusion: LCRP combined with case-based health education could significantly improve hypertensive patients’ MA.